2014
DOI: 10.1371/journal.pone.0099895
|View full text |Cite
|
Sign up to set email alerts
|

Association of Admission Serum Calcium Levels and In-Hospital Mortality in Patients with Acute ST-Elevated Myocardial Infarction: An Eight-Year, Single-Center Study in China

Abstract: ObjectiveThe relationship between admission serum calcium levels and in-hospital mortality in patients with acute ST-segment elevation myocardial infarction (STEMI) has not been well definitively explored. The objective was to assess the predictive value of serum calcium levels on in-hospital mortality in STEMI patients.MethodsFrom 2003 to 2010, 1431 consecutive STEMI patients admitted to the First Affiliated Hospital of Nanjing Medical University were enrolled in the present study. Patients were stratified ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 30 publications
(27 reference statements)
4
39
0
2
Order By: Relevance
“…Similarly, Miura et al reviewed patients with heart failure and chronic kidney disease and reported that cardiac and all-cause mortality was significantly higher in the low-Ca group compared to the normal-high Ca group 27 . Finally, in patients with ST-elevated myocardial infarction lower Ca levels at the time of admission were associated with higher in-hospital mortality 28 . An important caveat to majority of the above mentioned studies is the focus on overall cardiovascular disease mortality, with limited data on association of Ca levels specifically with SCA.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Miura et al reviewed patients with heart failure and chronic kidney disease and reported that cardiac and all-cause mortality was significantly higher in the low-Ca group compared to the normal-high Ca group 27 . Finally, in patients with ST-elevated myocardial infarction lower Ca levels at the time of admission were associated with higher in-hospital mortality 28 . An important caveat to majority of the above mentioned studies is the focus on overall cardiovascular disease mortality, with limited data on association of Ca levels specifically with SCA.…”
Section: Discussionmentioning
confidence: 88%
“…Ca intake or level has mainly been studied in relation to bone health and in regards to its supplementation and cardiovascular safety 18 . Nevertheless, multiple cohort studies with long duration of follow up using baseline Ca levels have investigated the association of Ca serum levels and cardiovascular or all-cause mortality in different populations and subgroups 1928 . These reports demonstrated conflicting results, with both high and low levels of Ca reported to be associated with increase in cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recently, hypocalcemia has been reported to be a predictor of increased in-hospital mortality in patients with severe coronary artery disease (CAD). 9 However, the association between serum calcium and the GRACE score remains unclear to date.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of serum calcium show no association with calcification [21][22][23][24][25] , although some show a positive correlation with presence, extent and progression of AAC in older adults 19,[26][27] , with mixed results for presence of CAC, although there may be an association with extent or progression [18][19][28][29] . Serum calcium was an independent predictor of calcified and mixed plaque but not non-calcified plaque 29 and higher concentrations were associated with lower in-hospital mortality among MI patients 30 . Nevertheless, serum calcium levels often bear little relationship to intake, as is evidenced by the study by Wang et al, where higher serum calcium was associated with increased AAC but a higher calcium intake was found in those with no AAC 19 .…”
Section: Calcificationmentioning
confidence: 88%